Development of an Encyclopedia Based on the Local Potential of Batang Gadis National Park (BGNP) as a Learning Resource on Biodiversity for Grade X Senior High School Students - Hafizah, Nurhafizah Nasution; Syarifah Widya Ulfa (Universitas Negeri Semarang, 2025)
This research aims to develop a biodiversity encyclopedia based on the local potential of Batang Gadis National Park (BGNP) as a learning resource for Grade X students of general Senior High Schools (SMA) and Islamic Senior High Schools (MA). This research is driven by the lack of biodiversity supporting learning resources other than textbooks and student worksheets, where, for every biodiversity material, teachers have to print original pictures of plants/animals along with their morphological characteristics. This research used the Research and Development (R&D) method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The study was conducted from April to August 2025 at MAN 1 Mandailing Natal. Data collection was carried out through literature review, interviews, and validation questionnaires for material, media, and practicality from biology teachers and students. The data were analyzed quantitatively using a validity formula complemented with criteria, processed through Excel. The research results showed that the material expert validation was 97% (very valid), media expert validation was 100% (very valid), teacher practicality was 97% (very valid), and the small-scale trial of the encyclopedia product obtained a percentage of 94% (very good). Therefore, it can be concluded that the biodiversity encyclopedia of Batang Gadis National Park, Mandailing Natal, is feasible to be implemented as a supplementary learning resource.